Charge redistribution in QM:QM ONIOM model systems: a constrained density functional theory approach. (17th November 2017) - Beckett, Daniel; Krukau, Aliaksandr; Raghavachari, Krishnan
ABSTRACT: The ONIOM hybrid method has found considerable success in QM:QM studies designed to approximate a high level of theory at a significantly reduced cost. This cost reduction is achieved by treating only a small model system with the target level of theory and the rest of the system with a low, inexpensive, level of theory. However, the choice of an appropriate model system is a limiting factor in ONIOM calculations and effects such as charge redistribution across the model system boundary must be considered as a source of error. In an effort to increase the general applicability of the ONIOM model, a method to treat the charge redistribution effect is developed using constrained density functional theory (CDFT) to constrain the charge experienced by the model system in the full calculation to the link atoms in the truncated model system calculations. Two separate CDFT-ONIOM schemes are developed and tested on a set of 20 reactions with eight combinations of levels of theory. It is shown that a scheme using a scaled Lagrange multiplier term obtained from the low-level CDFT model calculation outperforms ONIOM at each combination of levels of theory from 32% to 70%. Abstract :